2013
DOI: 10.1186/1756-9966-32-25
|View full text |Cite
|
Sign up to set email alerts
|

Tau protein as a potential predictive marker in epithelial ovarian cancer patients treated with paclitaxel/platinum first-line chemotherapy

Abstract: BackgroundThe aim of the study was to evaluate predictive and prognostic significance of microtubule-associated protein Tau in epithelial ovarian cancer (EOC) patients treated with paclitaxel and platinum-based chemotherapy.Methods74 patients with EOC (stage I-IV) who underwent cytoreductive surgery followed by standard paclitaxel/platinum chemotherapy were included in the retrospective analysis. Their formalin-fixed, paraffin-embedded tissue specimens were immunohistochemically stained for Tau protein, using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
74
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 60 publications
(75 citation statements)
references
References 19 publications
1
74
0
Order By: Relevance
“…The PFS of the Tau‐negative patients was significantly better than that of the Tau‐positive patients ( P =.0355). In the univariate analysis, the 3 year OS of the Tau‐negative patients was significantly better than that of the Tau‐positive patients ( P =.0198) 4. However, in the multivariate analysis, there was no significant difference 4.…”
Section: Discussionmentioning
confidence: 88%
See 4 more Smart Citations
“…The PFS of the Tau‐negative patients was significantly better than that of the Tau‐positive patients ( P =.0355). In the univariate analysis, the 3 year OS of the Tau‐negative patients was significantly better than that of the Tau‐positive patients ( P =.0198) 4. However, in the multivariate analysis, there was no significant difference 4.…”
Section: Discussionmentioning
confidence: 88%
“…In the univariate analysis, the 3 year OS of the Tau‐negative patients was significantly better than that of the Tau‐positive patients ( P =.0198) 4. However, in the multivariate analysis, there was no significant difference 4. It was concluded that negative Tau protein expression seems to be both a good prognostic factor and a predictor of the response to paclitaxel and platinum‐based chemotherapy in patients with epithelial OC 4.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations